A ROS‐Activatable Agent Elicits Homologous Recombination DNA Repair and Synergizes with Pathway Compounds. Issue 17 (2nd November 2015) - Thowfeik, Fathima Shazna; AbdulSalam, Safnas F.; Wunderlich, Mark; Wyder, Michael; Greis, Kenneth D.; Kadekaro, Ana L.; Mulloy, James C.; Merino, Edward J.
Abstract: We designed ROS‐activated cytotoxic agents (RACs) that are active against AML cancer cells. In this study, the mechanism of action and synergistic effects against cells coexpressing the AML oncogenes MLL‐AF9 fusion and FLT3‐ITD were investigated. One RAC (RAC1 ) had an IC50 value of 1.8±0.3 μm, with ninefold greater selectivity for transformed cells compared to untransformed cells. Treatment induced DNA strand breaks, apoptosis, and cell cycle arrest. Proteomics and transcriptomics revealed enhanced expression of the pentose phosphate pathway, DNA repair, and pathways common to cell stress. Western blotting confirmed repair by homologous recombination. Importantly, RAC1 treatment was synergistic in combination with multiple pathway‐targeting therapies in AML cells but less so in untransformed cells. Together, these results demonstrate thatRAC1 can selectively target poor prognosis AML and that it does so by creating DNA double‐strand breaks that require homologous recombination. Abstract : RAC 'em and stack 'em : We have designed ROS‐activated cytotoxic agents (RACs) that target acute myeloid leukemia cells. Detailed biochemical studies showed that RACs induced AML cell survival through homologous recombination DNA repair. Inhibiting the survival mechanism caused greater synergistic effects in AML cells versus normal cells, thereby paving the way forward for RACs as therapeutic agents.